UJI TOKSISITAS EKSTRAK DAUN PLETEKAN (Ruellia tuberosa L.) DENGAN MENGGUNAKAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) - Nurhawa Vitalia; Ahmad Najib; Aktsar Roskiana Ahmad (Faculty of Pharmacy, Universitas Muslim Indonesia, 2016)
Minnie root (Ruellia tuberosa L.) belongs to Acanthaceae family. In traditional medicine has been used as diuretic, antidiabetic, antipyretic and antihypertensive and it also recently been incorporated as a component in a herbal tea in Taiwan. This research is aim to determine LC50 value of Minnie root leaves extract (Ruellia tuberosa L.) to Artemia salina Leach shrimp larvae. Dryed samples extracted by graduate maceration with n-hexan, ethyl acetate and ethanol respectively. Rendamen n-hexane extract obtained as much as 1.158%, ethyl acetate extract as much as 2.017% and ethanol extract as much as 3.669 %. Based on qualitative screening used TLC method, ethyl acetate extracts and ethanol extracts of Minnie root (Ruellia tuberosa L.) leaves contain alkaloid, saponin, flavonoid and phenolic compounds. Toxicity assay Artemia salina Leach shrimp larvae have been conducted on leaves extracts of Minnie root (Ruellia tuberosa L.). Toxicity assay on sample extract of Minnie root (Ruellia tuberosa L.) leaves determine by counting the number died of larvae after 24 hours treatment. LC50 on sample calculated by probit analysis method. The toxicity assay showed LC50 of ethyl acetate extracts and ethanol extracts are toxic with LC50 266.07 ± 0.93 µg/mL and 142.160 ± 1.30 µg/mL.